Radiation Physics and its Applications in Modern Radiotherapy Equipment - Mohammed, Mohammed Bassem; Mahdi, Mustafa Oday; Jabbar, Musa Basheer; Sahib, Muhammad Sadiq Ali Abdul; Khuder, Rihab Aziz (American Journal of Botany and Bioengineering, 2025)
With the emergence of a highly sophisticated and complex health system, exquisite methods had to be developed for the diagnosing and treatment needs of patients. One of these advancements was the initiation of using radioactive materials for medical purposes, also called radiotherapy (RT). Initial transmission to adopt this vague method had a lot of human casualties and unintended exposures to high-dose regions. By the invention of new generation healthcare equipment and highly sophisticated computer systems, RT was refined and became a common and routinely used method for treating various tumor types. Currently a treatment plan derived for one patient for a given time will be used as a reference for all patients treated with a system. All parameters affecting the plan will be monitored and confirmed, to be similar to the reference format. There are two major systems for administering RT treatment: teletherapy with high-energy X-rays or gamma-rays and brachytherapy with different energy gamma-ray sources. Teletherapy has become a routine technique and the number of RT treatment facilities has increased rapidly since the establishment of this technique. A minimum necessary condition for reliable treatment was the production of high dose rate teletherapy equipment which was done in many countries. With the establishment of computerized number crunching systems and three-devices, new and sophisticated techniques for treating with high-energy X-rays were developed and implemented. One of these advancements was a multi-leaf collimator (MLC) for conforming radiation doses to the shape of treatment volume (TV). Treatment technique, shielding and other requirements had to be calculated and drafted for each treatment plan (TP) which made this technique a very time-consuming process requiring long co-operation of a medical physicist (MP), oncologist and medical technical personnel (MTP). Thus, to facilitate using external RT treatment systems, a collection of codes was developed for implementing an easy, safe and done with a minimum time program for achieving fluency in treatment and including human resources and decreasing their time consumptions, costs and errors. The codes were written in the Pascal Delphi programming language and run on MS-DOS operating system. Different sets of applications were implemented, which concentrated on designing the fastest code with the most accuracy for a specific evaluation for an RT technique. With the first generation of MS-DOS operating systems, first applications were written in Basic computer programming language which became obsolete in a short time. This shortened life cycle caused great losses in both investments and time consumptions. To cover this weakness, and provide a compact system which is cheap, portable and still fluent, a new technique was developed in order to convert an application coded in Pascal Delphi programming language to that run on mobile phones. An application code, called RT Number Crunching, with a good technical performance, was developed for teletherapy systems of this type. It contained several applications for commonly run calculations, tables and notations with transparent operational steps for trained users. So far, there has been an installation version for central processing units (CPU) of the type of intel which can be used on MS window operating systems of computers, with a good success, usage and good comments from users. A mobile phone version, compatible with Android operating systems, was coded using Java-scripting language. This code provided users great advantages due to its own nature of mobile phones such as being cheap, portable and easy usage. The first fully code run program, compared to application “Didactic”, was “Specific” that was specially coded for a detailed calculation in non-standard procedures, external beam brachytherapy systems and seed-pulse gamma-ray brachytherapy teletherapy systems. Both of these phone and computer codes are applicable and run in treatment facilities for both brachytherapy systems. A computer version of “Integration” was developed and just entered fixed numerical data and coded all follow-up settings. It cuts all procedural steps and saves a minimum time for obtaining results. For use of portable and mobile computer facilities in hospitals, there would be some new versions to cover this request. All complied codes and applications of the software are available publicly for free or highly discounted because of their long time, great caution and high human costs for numerical evaluations in each treatment facility.